Avaliação do sistema de integração lavoura pecuária em função dos atributos físicos do solo no Município de Riacho dos Cavalos-PB - Costa, Claudinete Lígia Lopes (Universidade Federal Rural do Semi-Árido, 2012)
The integration crop-livestock is a system of use of the agricultural areas with management of crops and animals at same area, making possible, intensification of the use of the land, increasing the sustainable of the production systems and improving the profitability through the introduction of the tillage of annual pastures. The news inter-relations established with the presence of animals can make the soil the most complex. For this reason, techniques of management adapted for this system of production must be developed. This work analyzed the effect of the soil compaction, in function of the soil physical and mechanical characteristics in areas cultivated with corn and bean at the integration system crop-livestock. The experiment was managed at Riacho dos Cavalos- PB, in the period of March of 2011 October of 2011. The parameters of soil bulk density, structural void ratio and compression index of the soil were analyzed in the depths of 0.0 to 0.05m, 0.05 to 0.10m and 0.10 to 0.20m. The delineation in blocks at random was used in scheme factorial 2x4x3 with three repetitions. The results showed significant differences up for soil bulk density and structural void ratio. There was not increase of the soil bulk density as well as reduction of the soil structural void ratio with the bovine ones
Keywords: Manejo; Rentabilidade; Sustentabilidade; Management; Sustainable; Crop-livestock; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO